Effects and safety of Ophiocordyceps sinensis preparation in the adjuvant treatment for dialysis patients: a systematic review and meta-analysis - Liu, Meixi; Cui, Chengji; Chang, Tianying; Zhou, Qingshan; Cui, Yingzi; Zhang, Shoulin; Liao, Xing (Frontiers in Pharmacology, 2024)
Ethnopharmacological relevance: Ophiocordyceps sinensis (O. sinensis), a genus of ascomycete fungi, has been widedly used in China as a dietary supplement or natural remedy and intensively studied in various disease models with its immunomodulatory potentials.It is a rich source of various bioactive compounds and used for treating end-stage renal disease. This systematic review with clinical evidence aimed to highlight the efficacy and safety of O.Sinensis as an adjuvant treatment for patients undergoing dialysis.A systematic search through nine electronic databases up to April 31, 2024, was conducted for related studies. The Cochrane risk-of-bias tool was used to evaluate the quality of studies. The Grading of Recommendations Assessment, Development, and Evaluation system was used to assess the certainty of evidence. Two researchers independently searched the literature and evaluated the risk of bias.Results: After the screening, 35 randomized controlled trials (RCTs) involving 2914 patients were eventually included. The meta-analysis showed that using O. sinensis effectively reduced the following outcomes in patients undergoing dialysis: C-reactive protein (15RCTs, MD = -2.22, , 95% CI -3.24 to -1.20; very low certainty evidence); creatinine (22RCTs, MD =1.33, 95% CI -1.79 to -0.87 ; very low certainty evidence); blood urea nitrogen (21RCTs, MD =-1.57, 95% CI -2.07 to -1.07 ; low certainty evidence);. It could also effectively improve the following outcomes in patients undergoing dialysis: albumin (20RCTs, MD =-0.81, 95% CI -1.21 to -0.41; low certainty evidence); hemoglobin (19RCTs, MD =-1.00, 95% CI -1.43 to -0.57; low certainty